1992
DOI: 10.1111/j.1365-2141.1992.tb04595.x
|View full text |Cite
|
Sign up to set email alerts
|

Defects in type IIA von Willebrand disease: a cysteine 509 to arginine substitution in the mature von Willebrand factor disrupts a disulphide loop involved in the interaction with platelet glycoprotein Ib‐IX

Abstract: Type IIA von Willebrand disease (vWD) is characterized by the loss of high and intermediate weight multimers of von Willebrand factor (vWF) from plasma. The 3' end of exon 28 in the vWF gene from four type IIA vWD patients was amplified by the polymerase chain reaction, cloned and sequenced. Sequencing identified two potential missense mutations resulting in the amino acid substitutions Arg 834-->Gln and Glu 875-->Lys in the mature vWF subunit within an area of vWF where mutations in type IIA vWD have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Finally, several different single cysteine changes have been shown to alter the function of the homologous von Willebrand factor (Zhang et al 1994). Among them, a C509R substitution disrupts a disulphide loop involved in the interaction with platelet glycoprotein Ib-IX and causes a type IIA Willebrand disease (Lavergne et al 1992). A C2010R mutation in type IID von Willebrand disease causes defective dimerization of von Willebrand factor subunits (Schneppenheim et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several different single cysteine changes have been shown to alter the function of the homologous von Willebrand factor (Zhang et al 1994). Among them, a C509R substitution disrupts a disulphide loop involved in the interaction with platelet glycoprotein Ib-IX and causes a type IIA Willebrand disease (Lavergne et al 1992). A C2010R mutation in type IID von Willebrand disease causes defective dimerization of von Willebrand factor subunits (Schneppenheim et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…DDAVP-induced thrombocytopenia has previously been observed in other noncysteine type 2B gain-of-function mutations [26], but other reported cysteine mutations [14, 16] have not demonstrated gain-of-function in patients [15]. In agreement with our clinical data at "basal" times, the patient with a C1272R mutation reported by Lavergne et al also had low VWF:Ag = 30 U/dl, a VWF:RCo activity < 5, and absent RIPA, but a DDAVP trial was not performed [14]. Similar results were obtained from a patient with a C1272F mutation reported by Woods et al with low basal VWF:Ag = 32 U/dl, VWF:RCo/VWF:Ag ratio < 0.15 and absent RIPA at >1.5 mg/mL ristocetin [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, reduced and alkylated recombinant VWF shows an enhanced affinity for platelets in the absence of ristocetin [13]. Evidence for high affinity in VWD patients due to loss of the disulfide bond has not been previously observed [1416]. Here, evidence is presented from two patients which confirms that cysteine amino acid substitutions that break the disulfide bond induce a gain-of-function phenotype that manifests in a DDAVP-treatment-induced transient thrombocytopenia which promptly restores to a homeostasis of low VWF and normal platelet counts within hours following treatment [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…However, two other changes affecting the same codon, C1272G [11] and C1272R [12], were reported. Expression studies of these two mutants showed a VWF with an absence of intermediate and high molecular weight multimers.…”
Section: Discussionmentioning
confidence: 99%